Teaching english in public schools in Rio de Janeiro: an analysis of what teachers say about their practice - Danielle de Almeida Menezes; Isabela Vitória de Oliveira dos Santos (Corporación Universitaria Minuto de Dios, 2017)
This work aims to analyze the statements of English teachers to know the scientific conceptions destined to the teaching activity, the specialized and formalized knowledge, the curricular knowledge and the knowledge developed during the exercise of the profession that influence their professional practice. To accomplish this, six semi-structured interviews with public school teachers in the city of Rio de Janeiro were analyzed. The data were submitted to qualitative analysis. The results show that the performance of these professionals in the classroom is essentially pragmatic, being determined by the conditioning factors and the objectives inherent in the contexts in which they act.